Optimization of Fixed-Bed Sequencing Bio-Reactors Using Jute Fibre for Seafood Processing Wastewater Treatment - Zulkipli, Muhammad Asyraf; Abu Bakar, Juliza; Bakar, Mahbooba; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel (International Journal of Integrated Engineering, 2021)
Seafood processing wastewater has high contents of nitrogen and ammonia which are the key for occurring eutrophication. Therefore, the present study was performed to optimize the seafood processing wastewater treatment using activated sludge and jute fiber in the sequencing batch reactor (JF-SBR) compared to conventional SBR. The optimization was studied based on aeration and aeration time using response surface methodology. The results revealed that the JF-SBR has higher efficiency compared to the conventional SBR in the removal of BOD (66.86% vs. 53.52%), ammonia nitrogen (AN) (68.75% vs. 50.86%), COD (66.86% vs. 53.52%), TSS (95.65% vs. 78.26%), nitrite (100% vs. 50%), and nitrate (91.67% vs. 83.33%). The optimal removal of these parameters was recorded after 18.5 hrs with 44.14 L/min of aeration rate in both JF-SBR and SBR. These finding demonstrated that the JF-SBR is the viable option to treat seafood wastewater for safe disposal.